Revision Surgery for Idiopathic Macular Hole after Failed Primary Vitrectomy. (7th January 2021) - Lachance, Alexandre; You, Eunice; Garneau, Jérôme; Bourgault, Serge; Caissie, Mathieu; Tourville, Éric; Dirani, Ali
Abstract : Purpose . To investigate the anatomical and functional outcomes of revision surgery after failed primary surgery for idiopathic macular hole (MH). Methods . All consecutive patients with MH were identified from a cohort of patients operated between 2014 and 2018 at the CHU de Québec-Université Laval (Québec). The clinical and anatomical features of patients with unclosed MH after primary surgery were retrospectively collected. Our primary outcome was MH nonclosure rate after revision surgery. Our secondary outcomes were best-corrected visual acuity (BCVA) with ETDRS scale and MH size of eyes with revision surgery preoperatively and at 3 and 12 months after revision surgery. Results . In our cohort of 1085 eyes, 926 eyes met inclusion criteria and were analyzed in the study. We identified 22 eyes with failed primary surgery (2.4%), of which 20 underwent revision surgery. We had no bilateral MH in these 22 eyes. The nonclosure rate of MH after revision surgery was 15%. The mean final BCVA for closed MH after revision surgery was 55 ± 19 letters. Compared to the initial presentation, the mean change in visual acuity (VA) for closed MH was +4 ± 31 letters and +16 ± 17 letters at 3 and 12 months after the revision surgery, respectively. At initial presentation, patients with failed primary surgery had a baseline MH size of 665 ± 226  μ m. The mean MH size after failed primary surgery was 607 ± 162  μ m and 546 ± 156  μ m for the three unclosed MHs one month after revision surgery. Conclusion . The success rate of revision surgery in eyes with unclosed MH is 85%. After successful revision surgery, eyes demonstrated an improvement in VA and closure of the MH.